2019
DOI: 10.20429/ger.2019.160201
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of High School Female and Minority Self-efficacy and Interest in STEM in Chatham County, Georgia

Abstract: With the growing demand for science, technology, engineering, and mathematics (STEM) jobs in the U.S., the attainment of college degrees in these areas is of paramount importance. Both federal and state governments have established initiatives to grow the number of STEM degrees earned by women and racial minorities, as these groups graduate in STEM disciplines and work in STEM fields at a lower rate than that of their majority counterparts. The factors that can deter women and underrepresented minorities from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Gremillion et. al [17] found difference in self efficacy in engineering and technology between men and women, with men having higher self-efficacy, however no difference was found in math and science. Lent et.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Gremillion et. al [17] found difference in self efficacy in engineering and technology between men and women, with men having higher self-efficacy, however no difference was found in math and science. Lent et.…”
Section: Introductionmentioning
confidence: 96%
“…Findings from a South Korean study [32] support this, having found no difference in self-efficacy between genders. However, other studies contradict these findings, focusing on mathematics self-efficacy and attitudes as correlated to choice of STEM major, and finding that men rate their efficacy in mathematics higher than women [17]. It is also important to look at SES as a factor as higher SES students tend to have higher grades which may lead to higher reports of self-efficacy across disciplines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations